Kansas feeds for sheep - Munger, Lewis J. (My University, 1905)
Introduction: KANSAS AS A SHEEP FEEDING STATE. 1. The importance of the sheep feeding industry in the state results from a combination of natural conditions that has made Kansas one of the great meat producing states of the Union. This is well established by the facts that we are situated in a great alluvial plain noted for its production of cheap feed and surrounded by the climatic conditions which favor the grazing and feeding industry in all parts of the state. A long list of varieties of forage and grain crops are produced here at a minimum cost. Another great natural advantage is that our state lies between the great range country and the point where the meat grown on the range is consumed. Kansas has several great systems of railways traversing the state, entering the range country on our north, south and west, and converging at the commercial centers where are situated the great abattoirs which slaughter two-thirds of the meat produced for the world. Of these three natural conditions climate is the one of most importance. We have in Kansas that excellent climate that is just what a sheep needs to make the most gain out of every pound of feed eaten. Furthermore every scientific man knows that all feed produced on the farm must be consumes on it if the fertility of the land be maintained. We have not yet learned to appreciate the extent to which the employment of far labor in the care of live -stock during the winter season when it would otherwise be idle, has increased prosperity and made our agriculture stable.
Citation: Munger, Lewis J. Kansas feeds for sheep. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Comparisons of Kansas Feeds for Sheep; Indian Corn; Dry Versus Soaked Corn for Sheep; Theses